Rousseau, Rio, and the Green Economy - Lopes, Carlos (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2019)
The Social Contract by Jean-Jacques Rousseau emerges as the most compelling and seminal piece of political theory. It explores legitimate political order in the context of classical republicanism. This paper delves into the following questions around Rousseau’s thesis: What would Rousseau make of the contemporary multilateralist surveillance regime, gridlocked in key areas that have direct links with human security? How would he square with a society that seems to be at odds with the nature– society equilibrium that he staunchly advocated for? Will Rousseau be able to lift today’s generation out of the collective myopia that focuses on individualism as the gateway to a prosperous future?